Brief Report: Mortality After Loss to Follow-Up—A Linkage Study of People Living With HIV in Thailand and Malaysia. (1st November 2022) - Jiamsakul, Awachana; Gani, Yasmin; Avihingsanon, Anchalee; Azwa, Iskandar; Chaiwarith, Romanee; Khusuwan, Suwimon; Ross, Jeremy; Law, Matthew; Kiertiburanakul, Sasisopin
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: Linkage studies have reported high rates of previously unascertained mortality among people living with HIV (PLHIV) who have been lost to follow-up (LTFU). We assessed survival outcomes among PLHIV who were LTFU in Thailand and Malaysia, through linkages to a national death registry or HIV database. Methods: Data linkages with the national death registry or national HIV database were conducted in 2020 on all PLHIV who met LTFU criteria while enrolled in care at participating HIV clinical sites. LTFU was defined as having no documented clinical contact in the previous year, excluding transfers and deaths. Survival time was analyzed using the Cox regression, stratified by site. Results: Data linkages were performed for 489 PLHIV who had been LTFU at sites in Malaysia (n = 2) and Thailand (n = 4). There were 151 (31%) deaths after being LTFU; the mortality rate was 4.89 per 100 person-years. Risk factors for mortality after being LTFU were older age [41–50 years: hazard ratio (HR) = 1.99, 95% confidence interval (CI): 1.08 to 3.68; and older than 50 years: HR = 4.93, 95% CI: 2.63 to 9.22; vs. age 30 years or younger]; receiving NRTI + PI (HR = 1.87, 95% CI: 1.22 to 2.85 vs. NRTI + NNRTI); positive hepatitis C antibody (HR = 2.25, 95% CI: 1.40 to 3.62); and having previous AIDS illness (HR = 1.45, 95% CI: 1.03 to 2.05). An improved survival was seen with a higher CD4 count (CD4 351–500 cells/µL: HR = 0.40, 95%CI: 0.21–0.76; and CD4 >500 cells/µL: HR = 0.43, 95%CI: 0.25–0.75; vs. CD4 ≤200 cells/µL). Conclusions: Almost one-third of PLHIV who were LTFU in this cohort had died while out of care, emphasizing the importance of efforts to reengage PLHIV after they have been LTFU and ensure they have access to ongoing ART.